CORRELATION OF PROCALSITONIN LEVEL WITH SEPSIS DEGREES BASED ON SOFA SCORE - Citra Novita; Soeprapto Maat; Betty Agustina Tambunan (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2019)
Background. Sepsis is defined as a life-threatening organ dysfunction condition caused by dysregulation of host response towards infection. Sepsis is one of the leading causes of death in medical emergency. A recent study revealed 18 millions of sepsis occur annually with a mortality rate of 30%, so early diagnosis in assessing sepsis severity is necessary as a guide for early and specific therapy. Organ dysfunction in sepsis patients is associated with high mortality, assessed by Sequential Organ Failure Assessment (SOFA) criteria. Procalcitonin is widely used for diagnosing, monitoring, and prognosis sepsis.Aim This study aimed to analyze the correlation of procalcitonin level with sepsis severity based on SOFA score.  Method. This was an observational cross-sectional study. Samples were collected from December 2017-February 2018 of 72 patients. Each patient was calculated by SOFA score and underwent procalcitonin examination using an immunochromatography method by RAMP. Results. Samples from 72 patients who met the criteria, were analyzed consisting of 37 mailes(51.4%) and 35 females(48.6%), aged 23-77 years, with mean±SD 47.4±14.02 years. The range of SOFA score was 0-16 with mean±SD 6.47±3.61, while procalcitonin levels 0.20-200 ng/mL mean±SD 21.03±14.63 ng/mL. There was a significant correlation between procalcitonin level and SOFA score (r=0.752;p<0.0001).Discussion. This suggests that procalcitonin may illustrate the severity of sepsis patients. The higher the procalcitonin, the more severe the sepsis.Conclusions and recommendations. SOFA score and procalcitonin examinations should be performed routinely in patients with sepsis to assess prognosis (severity) for earlier pretreatment so that the mortality rate can be lowered.